Editorial - Manickam, Thomas (Journal of Dharma, 1987)
Life is exhibited by beings through signs of actions which indicate unity, harmony, purpose and meaning in the Universe. These actions couldbe sequenced as follows: inspiration, impulse, vibration, pulsation, respiration, circulation, introspection, reflection, co-ordination, direction andorientation. This series of actions which are specifically of living beings are dynamically open to fulfilment, expansion, growth, achievement, alteration, 'diversification, improvement and innumerable ways of adaptation to the changing habitats. Phenomenologically these signs of life are attributedto the rhythm (flam) of Nature. So they are said to be natural behavioural patterns of 1iving beings, botanically. zoologically and anthropologically.